Development of coffee-flavored nata de coco in syrup - Lim, Stephanie Lu
ABSTRACT Coffee-flavored nata de coco in syrup was developed intended for use in coffee jelly beverage. The effects of concentration of coffee (3. 4.5 and 6%) and soaking time (3, 5 and 7 days) on overall acceptability, color, sweetness, flavor and aroma of the product were investigated. The data were analyzed using the software STATISTICA VERSION 5.0 (mean scores, ANOVA and DMRT). Results indicated that concentration and soaking time did not significantly affect the sensory quality and consumer acceptability of the product. Coffee-flavored nata de coco in syrup that is acceptable to consumers may be produced by soaking in 3% coffee for three days.